Phytochemical content, antioxidant activity, and enzyme inhibition effect of Salvia eriophora Boiss. & Kotschy against acetylcholinesterase, a-amylase, butyrylcholinesterase, and a-glycosidase enzymes - Bursal, Ercan; Aras, A.; Kılıç, Ö.; Taslimi, P.; Gören, A.C.; Gülçin, İ. (Blackwell Publishing Ltd, 2019)
Many taxa of Salvia genus have been used in herbal beverages, food flavoring, cosmetics, and pharmaceutical industry. In this paper, chemical compounds of Salvia eriophora (S. eriophora) leaves were determined by LC–MS/MS (Liquid Chromatography tandem Mass Spectrometry). Salvigenin (158.64 ± 10.8 mg/kg), fumaric acid (123.09 ± 8.54 mg/kg), and quercetagetin-3.6-dimethylether (37.85 ± 7.09 mg/kg) were detected as major compounds in the ethanol extract, whereas fumaric acid (555.96 ± 38.56 mg/kg), caffeic acid (103.62 ± 20.51 mg/kg), and epicatechin (83.19 ± 8.43 mg/kg) were detected as major compounds in the water extract. Furthermore, enzyme inhibition of S. eriophora against acetylcholinesterase (AChE), ?-amylase (AM), butyrylcholinesterase (BChE), and ?-glycosidase (AG) enzymes were detected. AChE, BChE, AG, and AM enzymes were very strongly inhibited by S. eriophora water extract (WES) and S. eriophora methanol extract (MES). Additionally, antioxidant potential of S. eriophora was determined by in vitro analytical methods. IC 50 values of WES and MES were performed for radicals. Practical applications: Metabolic enzymes have crucial functions on living systems due to inhibition or activation of them mainly attributed with some health disorders. AChE, BChE, AM, and AG enzymes have important roles on carbohydrate metabolism or cholinergic pathways. The relation between enzyme inhibition effect and phenolic compounds or antioxidant activity need to be confirmed. Thus, many studies tested to clarify this relation for pure samples or plant extracts. To the best of our knowledge, this is the first report about inhibition effects of Salvia eriophora extracts against AChE, BChE, AM, and AG enzymes as well as their phenolic contents and antioxidant activities. © 2019 Wiley Periodicals, Inc.
Keywords: antioxidant; cholinesterase; enzyme inhibition; a-amylase; a-glycosidase; Amylases; Antioxidants; Enzyme activity; Extraction; Flavonoids; Liquid chromatography; Mass spectrometry; Metabolism; Plant extracts; Anti-oxidant activities; Antioxidant potential; Butyrylcholinesterase; Carbohydrate metabolism; cholinesterase; Glycosidases; Liquid chromatography-tandem mass spectrometry; Pharmaceutical industry; Enzyme inhibition; acetylcholinesterase; amylase; antioxidant; cholinesterase; cholinesterase inhibitor; glycosidase; phytochemical; plant extract; chemistry; kinetics; Salvia; Acetylcholinesterase; alpha-Amylases; Antioxidants; Butyrylcholinesterase; Cholinesterase Inhibitors; Glycoside Hydrolases; Kinetics; Phytochemicals; Plant Extracts; Salvia